2005
DOI: 10.1091/mbc.e04-11-1019
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition ofPkhd1Impairs Tubulomorphogenesis of Cultured IMCD Cells

Abstract: Fibrocystin/polyductin (FPC), the gene product of PKHD1, is responsible for autosomal recessive polycystic kidney disease (ARPKD). This disease is characterized by symmetrically large kidneys with ectasia of collecting ducts. In the kidney, FPC predominantly localizes to the apical domain of tubule cells, where it associates with the basal bodies/primary cilia; however, the functional role of this protein is still unknown. In this study, we established stable IMCD (mouse inner medullary collecting duct) cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 41 publications
5
66
0
Order By: Relevance
“…Lack of FPC downregulates Pkd2-channel activities in either the Pkhd1-knockout renal epithelial cells in primary culture or the Pkhd1-knockdown IMCD cells that we generated previously. 39 Given that FPC and PC2 physically interact and that the lack of FPC downregulates PC2 expression in vivo but PC2 does not downregulate FPC, we speculate that PC2 may function immediately downstream of FPC.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Lack of FPC downregulates Pkd2-channel activities in either the Pkhd1-knockout renal epithelial cells in primary culture or the Pkhd1-knockdown IMCD cells that we generated previously. 39 Given that FPC and PC2 physically interact and that the lack of FPC downregulates PC2 expression in vivo but PC2 does not downregulate FPC, we speculate that PC2 may function immediately downstream of FPC.…”
Section: Discussionmentioning
confidence: 84%
“…48 Our previous in vitro study also demonstrated that renal epithelial IMCD cells with downregulated FPC exhibit aberrant migratory polarity and lose the ability to drive collective cell migration, suggesting that the planar cell polarity also might be disrupted. 39 Aberrant planar cell polarity seen in cells with Pkhd1 defects suggests that ciliary defects in our Pkhd1 mutant mice might be caused by impeding orientally centriole arrangement and disabling the establishment of epithelial polarity. 39,49 Because our Pkhd1 mutant mice bear an in-frame GFP reporter, immunostaining with anti-GFP antibodies provided an FPC expression profile in affected tissues.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations